A comparative study of operative and conservative treatment of intraarticular displaced calcaneal fractures - K. Ramachandra Kamath (Nature Portfolio, 2021)
Abstract The treatment of intra-articular displaced calcaneal fracture is debatable. We conducted a prospective study to compare operative and non-operative treatment for intra-articular displaced calcaneal fractures. Patients were assigned to two groups based on the treatment given (operative and nonoperative) and were regularly followed for a period of 1 year. The outcome measures were assessed by Modified Rowe’s Score (MRS), Visual Analogue e Scale (VAS) and The American Orthopaedic Foot and Ankle Society (AOFAS) scale. The outcome related to patient’s job was noted after one year and compared with pre-injury status. Fifty five patients with 61 calcaneal fractures were studied. Thirty of them were operated and 31 were treated conservatively. Out of 30 operated cases, Bohler’s angle was restored in 25 cases and these had good results with all three outcome scores at 1 year follow up and remaining 5 cases showed fair results (Mean MRS: 74.783, VAS: 3.348, AOFAS: 78.783). Thirty one cases treated with cast also showed fair results (Mean MRS: 57.368, VAS: 4.944, AOFAS: 71.211). The overall outcome of operated cases were better than non-operated cases (unpaired T test MRS: 5.807 p < 0.001, VAS: 4.387 p < 0.001, AOFAS: 2.728 p = 0.008) . Operative treatment of displaced intra-articular calcaneal fractures gave good results at one year follow up, provided Bohler’s angle was restored to normal range. Non operative treatment gave fair results. Complications were seen both with operative and non-operative treatment.